Redefine Anxiety: A Message of Hope - Hunt, Sebastián (Allies for Education, 2017)
Think of your earliest memory in life; for some it may be your first birthday or your first steps. I remember growing up with a loving, supportive family. But my first memory is not something I experienced with them. I remember my very first anxiety attack. I was only in Kindergarten but I remember every single detail. This is my story...